Geriatric Nutrition Risk and Creatinine Indexes in Estimating the Nutritional Status of Elderly Hemodialysis Patients: GNRI and CI in Estimating the Nutritional Status of Elderly Hemodialysis Patients - Yakaryılmaz, Funda Datlı; Pembegül, Irem (Progress in Nutrition, 2022)
Objective: Malnutrition is a common complication in hemodialysis (HD) patients, although it cannot be evaluated adequately due to the limitations of available malnutrition screening tools. The aim of our study is to evaluate the relationship between Mini nutritional Assessment-Short Form (MNA-SF) and objective malnutrition tool Geriatric Nutritional Risk Index (GNRI) and Creatinine Index (CI) in HD patients.Methods: This is a cross-sectional study of 129 patients aged 65 years and older (female=61 (47.3%) and male=68 (52.7%), 68.88 ± 7.24 years) receiving maintenance HD therapy. Malnutrition was diagnosed with MNA-SF. GNRI and CI were calculated using existing formulas.Results: Of the participants, 26 (20.15%) were diagnosed with severe malnutrition, 25 patients (19.4%) were at risk of malnutrition and 78 (60.45%) were diagnosed with normal nutritional status. The optimal cut-off value for GNRI